Nystagmus of Pelizaeus-Merzbacher Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
Magnetic search-coil oculography of three brothers, aged 20, 22, and 25, with Pelizaeus-Merzbacher disease (PMD) was used to demonstrate nystagmus not obvious on inspection at the W. K. Kellogg Eye Center, University of Michigan, Ann Arbor, MI.